2010
DOI: 10.3846/ijspm.2010.02
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomic Field Investigation in to Induced Bias in Residential Real Estate Appraisals

Abstract: ABstRACt.A taxonomic approach to field research was developed and utilized to support empirical and experimental research findings into the impact that incentives/pressures to overvalue have on systematic valuation bias. An expected no-bias population was defined and valuation judgments from actual, real-world appraisals were statistically tested against it. The judgments of appraisers presented with no incentive/pressure to over-value were consistent with the no-bias population, while the judgments of apprais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Only 21 (15.9%) indicated a weak effect, with Overall, the survey results confirm that client influence is a problem in Kenya's valuation profession that contributes to inaccurate valuation outcomes. This finding reinforces the findings of Crosby et al (2018), Diaz and Hansz (2010), and Zhu and Pace (2010), who established that client influence negatively impacts the valuation profession contributing to valuation inaccuracies in the UK and USA. Further, this finding is in line with the findings of Ashaolu and Olaniran (2015) and Amidu et al (2008), who found that client influence is a major problem posing a negative impact on the valuation profession in Nigeria.…”
Section: Survey Results: Registered and Practising Valuerssupporting
confidence: 89%
See 4 more Smart Citations
“…Only 21 (15.9%) indicated a weak effect, with Overall, the survey results confirm that client influence is a problem in Kenya's valuation profession that contributes to inaccurate valuation outcomes. This finding reinforces the findings of Crosby et al (2018), Diaz and Hansz (2010), and Zhu and Pace (2010), who established that client influence negatively impacts the valuation profession contributing to valuation inaccuracies in the UK and USA. Further, this finding is in line with the findings of Ashaolu and Olaniran (2015) and Amidu et al (2008), who found that client influence is a major problem posing a negative impact on the valuation profession in Nigeria.…”
Section: Survey Results: Registered and Practising Valuerssupporting
confidence: 89%
“…Similarly, Klamer et al (2019) and Achu et al (2015) indicated the existence of client influence in Netherlands and Malaysia, respectively. In the USA, Diaz and Hansz (2010) and Zhu and Pace (2010) established that appraisers succumb to client influence resulting in biased appraisals. Additionally, Ashaolu and Olaniran (2015), Amidu et al (2008) and Oshiobugie et al (2017) found that valuers succumb to client influence contributing to valuation inaccuracies in Nigeria.…”
Section: Interview Results: Professional Bodiesmentioning
confidence: 99%
See 3 more Smart Citations